Factors that influence acceptance of QR payment among customers in Malaysia - Lee, Hai Wen (2024)
This research aims to examine the factors that influence acceptance of QR payment among customers in Malaysia. The independent variables are perceived usefulness, ease to use, trust and compatibility while the dependent variable is intension to use QR payment. This research has determined the relationship between independent variables and dependent variable.